Pendidikan Politik dari Partai Demokrasi Indonesia Perjuangan (PDIP) Kepada Generasi Muda di Kabupaten Halmahera Utara - Laurens J. Lain (CV. Ulil Albab Corp, 2023)
This research explores the political education of the Indonesian Democratic Party of Struggle (PDIP) to the younger generation in North Halmahera Regency. An interview with the Chairman of the DPC PDI-P North Halmahera showed that PDIP recognizes the importance of political education to increase political awareness and community participation. The party carries the ideology of